1997
DOI: 10.1037/0021-843x.106.1.117
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year longitudinal study of body weight, dieting, and eating disorder symptoms.

Abstract: This article describes a 10-year longitudinal study of eating attitudes and behaviors. A sample of 509 women and 206 men completed a detailed survey in 1982 while they were in college. The authors contacted participants 10 years later and administered a 2nd questionnaire to assess stability and change in eating behaviors that occurred during the transition to early adulthood. Women in the study had substantial declines in disordered eating behavior as well as increased body satisfaction. However, body dissatis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
149
7
5

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(180 citation statements)
references
References 40 publications
15
149
7
5
Order By: Relevance
“…They were invited to participate in the study if they met study criteria for normal weight (body mass index [BMI] between 19 and 24 kg/m 2 ) or for overweight (BMI greater than or equal to 27.5 kg/m 2 ). To ensure that the two groups were distinct, study criteria for weight categories were slightly more stringent than U.S. federal guidelines for normal weight (BMI between 18 and 25 kg/m 2 ) and overweight (BMI greater than or equal to 25 kg/m 2 ; Lean, Han, & Seidell, 1999 (Heatherton, Mahamedi, Striepe, Field, & Keel, 1997;Williamson, Kahn, Remington, & Anda, 1990). However, within gender, age did not differ significantly between overweight and normal weight men (36.3 [12.7] vs. 32.2 [11.4] years; t (39) ¼ 1.1, NS), and there was only a trend-level difference between overweight and normal weight women (35.1 [13.8] vs. 27.8 [11.2] years; t (37) ¼ 1.9, p ¼ 0.07).…”
Section: Participantsmentioning
confidence: 99%
“…They were invited to participate in the study if they met study criteria for normal weight (body mass index [BMI] between 19 and 24 kg/m 2 ) or for overweight (BMI greater than or equal to 27.5 kg/m 2 ). To ensure that the two groups were distinct, study criteria for weight categories were slightly more stringent than U.S. federal guidelines for normal weight (BMI between 18 and 25 kg/m 2 ) and overweight (BMI greater than or equal to 25 kg/m 2 ; Lean, Han, & Seidell, 1999 (Heatherton, Mahamedi, Striepe, Field, & Keel, 1997;Williamson, Kahn, Remington, & Anda, 1990). However, within gender, age did not differ significantly between overweight and normal weight men (36.3 [12.7] vs. 32.2 [11.4] years; t (39) ¼ 1.1, NS), and there was only a trend-level difference between overweight and normal weight women (35.1 [13.8] vs. 27.8 [11.2] years; t (37) ¼ 1.9, p ¼ 0.07).…”
Section: Participantsmentioning
confidence: 99%
“…While experimental manipulations of dietary restriction have demonstrated the expected result that dietary restriction produces weight loss (Ditschuneit & Flechtner-Mors, 2001;Presnell & Stice, 2003;Wadden et al, 2004), some studies of naturalistic dietary restriction have yielded counterintuitive findings whereby dietary restriction predicts an increase, rather than a decrease, in body mass (e.g., Field et al, 2003;Klesges, Isbell, & Klesges, 1992;Neumark-Sztainer et al, 2006) or fails to predict change in body mass over time (Heatherton, Mahamedi, Striepe, Field, & Keel, 1997). Possible explanations of this finding include the questionable validity of some self-report measures of dietary restriction (Stice, Fisher, & Lowe, 2004) and the tendency toward disinhibition (i.e., binge eating), which covaries with dietary restriction and may be the critical variable that is responsible for weight gain (van Strien, Engels, van Staveren, & Herman, 2006).…”
mentioning
confidence: 99%
“…Although males have been shown to weigh more than females, the female-to-male ratios of clinical and subclinical eating disorders is about 9:1 and 3:1, respectively (Levine & Piran, 2004). Females are most likely to experience subsequent increases in body dissatisfaction and eating disorders during and following puberty (Heatherton, Mahamedi, & Striepe, 1997), which also corresponds to confusion surrounding identity, self-esteem, and social acceptance (Thompson, Coovert, & Stormer, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…At any point in time, 40-45% of girls and young women are trying to lose weight through various means motivated by "normative" body dissatisfaction (French, Story, & Neumark-Sztainer, 1997;Striegel-Moore, Silberstein, & Rodin, 1986). Killen, Hayward, & Taylor, 1998), and prevalence rates are much higher among female college students than in the general population or among men (Dancyger & Garfinkel, 1995).Longitudinal studies have shown that women in college are more likely to identify themselves as overweight, report higher body dissatisfaction, and be at greater risk to engage in disordered eating than women who are not (Heatherton et al, 1997;Vohs, 2001). Moreover, many college students experiencing disordered eating behaviors doubt their symptoms warrant treatment and thus do not pursue therapy (Becker, Franko, Nussbaum, & Herzog, 2004;Meyer, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation